Synthesis and Applications of ZnV2O6 Nanomaterials. Issue 1 (10th September 2021) - Yang, Anqi; Luo, Jiaolian; Xie, Zhenyu
Abstract: ZnV2 O6 nanomaterials have attracted great interest in the fields of photocatalysis, sensors, solar cells, supercapacitors, and so on. Some investigators already feel that access to morphology controlled ZnV2 O6 is becoming more difficult to obtain, potentially limiting research. For good the optical, electrical, and surface properties, it is critical that ZnV2 O6 have a good performance in various applications. This review focuses on the various creative methods for the synthesis and the various applications of ZnV2 O6 nanomaterials. As promising materials, ZnV2 O6 have demonstrated great potentials in various applications, because of their electrical, optical, and catalytic properties. Besides, we also put forward some views on the challenges and new directions in this field and hoped that this paper can provide some useful information for future research about the design, synthesis and application of ZnV2 O6 nanomaterials.